Learners’ Attitudes towards Teachers’ switching to the mother tongue. The Case of Secondary school learners in Algeria - Mouleme Manel; Ahdi Hassan; Hakim Ali Buriro (Institut Agama Islam Negeri Palopo, 2019)
The current study investigated learners views towards the teachers' switching to the mother tongue in English as a foreign language (EFL) classes in secondary school in Algeria. It aimed at shedding some light on learners’ views towards the teachers’ switching to the mother tongue and different functions of code-switching (CS). A total of 120 secondary school learners participated in the study. The study concluded that learners have positive views toward the teachers' use of their mother tongue in EFL classes. It is used mainly to translate unknown vocabulary and explain grammar lessons.